Miskonsepsi Siswa pada Pemahaman Konsep Bangun Ruang - Arif Muchyidin; Lefi Nurlatif; Indah Nursuprianah (JRPM (Jurnal Review Pembelajaran Matematika), 2020)
The purpose of this study is to describe 8th-grade students’ misconceptions in solving surface area and volume of beam and cube problems and their causal factors. This is qualitative descriptive research. Based on the research, students’ misconceptions in solving surface area and volume of beam and cube problems are misconceptions on the concept of a beam, misconceptions on the concept of the cube, misconceptions on the concept of prerequisite material, misconceptions on unit comprehension, misconceptions on the understanding of meaning, and misconceptions on sign and number operations. While the causal factors of misconception are students’ assumptions about the lack of importance of concepts so students only memorize formulas, students are not able to associate one concept with other concepts, lack of understanding concepts in prerequisite material, misunderstanding the meaning of words in a problem, students have difficulty understanding pictures., misunderstanding the difference in the size of area and length.